Preparation and Electrochemical Properties of Mesoporous NiFe2O4/N-Doped Carbon Nanocomposite as an Anode for Lithium Ion Battery - Zhang, Jinli; Chen, Zi-He (Frontiers in Materials, 2020)
The NiFe2O4/nitrogen doped carbon composite was synthesized via calcination of NiFe-MOF in N2 atmosphere. Nitrogen-doped carbon not only improves the conductivity of the carbon-based material, but also provides pathway allowing Li+ diffusion rapidly during charge and discharge processes. The electrochemical data reveal that NiFe2O4/nitrogen-doped carbon nanocomposite deliver a capacity as high as 760 mAh∙g-1 at 0.2 C after 50 cycles, and show good rate performance by remaining a capacity of 600 mAh∙g-1 even at 1 C. The excellent electrochemical characteristics might be contributed to the NiFe2O4 ordered nanorod structure, well-marked porosity, and as well as the composition of nitrogen-doped carbon.